Welcome to Dragon Talk Inspiring Conversations about Dungeons and Dragons and the People Who Love to Play It. - Mazzanoble, Shelly (University of Iowa Press, 2022)
"In this collection, the hosts of "Dragon Talk," the official D and D podcast, recount some of the most inspiring stories from their guests. All use the core tenants of the game in their everyday life"--